KYAI ZAINUDDIN AMIR’S DA’WAH STRATEGY IN SPREADING ISLAMIC VALUES IN BADUY TRIBE COMMUNITY - Deden Mauli Darajat; Cinta Rahmi (Mimbar Agama Budaya, 2022)
Abstract. This article discusses to answer the question how is the strategy of Kyai Zainuddin Amir's da'wah in spreading Islamic values in the Baduy Tribe community? The Baduy tribe is an inland tribe located in Leuwidamar District, Lebak Regency, Banten Province, Republic of Indonesia. The Baduy tribe is divided into two, namely the Inner Baduy and the Outer Baduy. The results of this study indicate that Kyai Zainuddin Amir's missionary strategy is to use two approaches, the first is fardiyah propaganda or an interpersonal communication approach and the second is to establish the Sultan Hasanuddin Al-Jawi Modern Islamic Boarding School which is located around the Baduy community area in Lebak Regency, Banten Province. The Sultan Hasanuddin Al-Jawi Islamic Boarding School which he founded was part of Kyai Zainuddin Amir's da'wah strategy in spreading Islamic values to the Baduy tribe. A number of Baduy people choose Islam as their religion. Their Islamic procession was guided by Kyai Zainuddin Amir at his pesantren. The research methodology used in this study is a qualitative research methodology with a descriptive analysis approach. To obtain the validity of the data, the researcher will conduct in-depth interviews with sources relevant to the substance of the research problem. All data obtained in the form of documents, interviews, and observations were analyzed with a constructivist perspective.Keywords: strategy; da'wah; Kyai Zainuddin Amir; baduy tribeAbstrak. Artikel ini membahas menjawab pertanyaan bagaimana strategi dakwah Kyai Zainuddin Amir dalam menyebarkan nilai-nilai Islam pada masyarakat Suku Baduy? Suku Baduy adalah suku pedalaman yang terletak di Kecamatan Leuwidamar, Kabupaten Lebak, Provinsi Banten, Republik Indonesia. Suku Baduy terbagi menjadi dua, yaitu Baduy Dalam dan Baduy Luar. Hasil penelitian ini menunjukkan bahwa strategi dakwah Kyai Zainuddin Amir menggunakan dua pendekatan, yang pertama adalah dakwah fardiyah atau pendekatan komunikasi interpersonal dan yang kedua adalah mendirikan Pondok Pesantren Modern Sultan Hasanuddin Al-Jawi yang berlokasi di sekitar Baduy. masyarakat di Kabupaten Lebak, Provinsi Banten. Pesantren Sultan Hasanuddin Al-Jawi yang didirikannya merupakan bagian dari strategi dakwah Kyai Zainuddin Amir dalam menyebarkan nilai-nilai Islam kepada suku Baduy. Sejumlah orang Baduy memilih Islam sebagai agama mereka. Prosesi keislaman mereka dipandu oleh Kyai Zainuddin Amir di pesantrennya. Metodologi penelitian yang digunakan dalam penelitian ini adalah metodologi penelitian kualitatif dengan pendekatan deskriptif analisis. Untuk memperoleh keabsahan data, peneliti akan melakukan wawancara mendalam dengan narasumber yang relevan dengan substansi masalah penelitian. Semua data yang diperoleh berupa dokumen, wawancara, dan observasi dianalisis dengan perspektif konstruktivis.Kata Kunci: strategi; dakwah; Kyai Zainuddin Amir; suku baduy